Sub-divisional summer monsoon rainfall over India in relation to low pressure systems over the Bay of Bengal and adjoining land regions during 1982-1999 - MOHAPATRA , M. (MAUSAM, 2008)
A study is undertaken to find out characteristic features of relationship of the low pressure system (LPS) over the Bay of Bengal and adjoining land regions with the rainfall over different meteorological sub-divisions of India during summer monsoon season (June-September). For this purpose, rainfall over 35 meteorological sub-divisions in India and LPS days over west central (WC) Bay, northwest (NW) Bay, northeast (NE) Bay, Bangladesh (BDS), Gangetic West Bengal (GWB), Orissa, north coastal Andhra Pradesh (NCAP), east Madhya Pradesh and Chattisgarh (EMPC) and Jharkhand (JKD) during different monsoon months and the season as a whole over a period of 18 years (1982-1999) are analysed. There is large month to month variation in the impact of the LPS on the sub-divisional monsoon rainfall over India. However, the results presented in the study including developed correlation maps may be helpful to predict 24 hours rainfall based on the location of the LPS and associated monsoon trough. The frequent development and persistence of LPS over NW Bay are favourable for higher seasonal monsoon rainfall over east central India. The development and persistence of LPS over WC Bay adversely affect the seasonal rainfall over this region. On the other hand, the frequent development and persistence of LPS over WC Bay and its subsequent westward movement across NCAP are favourable for higher seasonal rainfall over the peninsular region excluding west coast. The seasonal rainfall over northwest India decreases with increase in LPS days over EMPC. The seasonal rainfall over west central India, northeast India and west coast are not significantly related with the number of LPS days over the regions under consideration.